Juventudes trabalhadoras, uberização e precarização da vida: contribuições para o campo do trabalho e da Terapia Ocupacional - Souza, Marina Batista Chaves Azevedo de (2020)
Scientific studies and statistical reports show that young people are living the most precarious paths in the world of work. To this population remains the deregulated work, including uberized work. The uberization process is one of the results of the flexible model of production, neoliberal rationality and the technological era. This process implies in the precariousness of the various life areas of the workers involved. The aim of this study was to understand the work reality of young people who perform informal or deregulated activities, as well as aspects related to their insertion and permanence in works of this type. The study followed the precepts of urban ethnography, used participant observation as a posture for insertion in the field as well as instruments for recording information such as field notebooks, questionnaires and audiovisual data. In-depth meetings are also held in this process. The participants were young food delivery working on digital platforms with 18-29 years old,. However, other informal jobs typically performed by young people were also analyzed during the ethnographic process. Data analysis followed the steps: a) Development of indexes; b) Preparation of titles and subtitles; c) Elaboration of the text. The results showed that the precocious, precarious, and destructive living conditions of young people are decisive in their insertion in the most diverse types of unregulated work. The institutions that support work and youth demonstrate many stereotypes about young workers and insufficient knowledge about their real-life situation, executing actions considered to be palliative, focused on professional education and entrepreneurship. It was possible to identify that due to their living and working conditions, uberized young workers experience problematic realities in the health, education and social relations. Thus, it is pointed out that the professions who acts in the field of work should provide an integral interdisciplinary and intersectoral care to these workers. This care should take place through the workers' health network, but also through the devices of education and social assistance, in conjunction with the legal agencies to support work and with representatives of social control, always considering the peculiarities of workers, including their age idiosyncrasies. The results helped to reflect on the need to expand Occupational Therapy practices in the field of work. Given the current situation, it is important that these practices, in addition to considering the real demands of workers in the various sectors and networks, have a political and critical character, in order to enable/facilitate access to information, awareness, social participation and the role of protagonist of these workers in the process of enabling their rights, as well as their collective articulations in favor of better working and living conditions.